The ex-utero intrapartum treatment (EXIT) strategy for fetal giant sacrococcygeal teratoma with cardiac insufficiency: A case report and review of the literature - Ding, Yunping; Yang, Mengmeng; Lv, Min; Jiang, Ying; Dong, Tian; Zhao, Baihui; Luo, Qiong (Frontiers in Oncology, 2022)
Background: Antenatally diagnosed sacrococcygeal teratoma has been associated with risks of perinatal complications and death, especially when the foetus has symptoms of cardiac insufficiency, hydrops or anemia in utero; however, the method of intervention remains controversial. Case:A 25-year-old pregnant woman was found to have a cystic and solid tumor in the fetal sacrococcygeal region at 16 weeks of gestation. As the tumour grew, the mother developed polyhydramnios accompanied with gestational diabetes. Fetal and tumorous hemodynamics were closely monitored by ultrasound. Abnormal cardiac function was detected at 31 weeks’ gestation, and we creatively performed pre-emptive delivery through the ex-utero intrapartum treatment with debulking. The teratoma was removed with utero-placental circulation support. The operation proceeded smoothly with favourable prognosis for both mother and newborn. Conclusion: The ex-utero intrapartum treatment may improve the prognosis for fetuses with heart failure when they reach viable gestation.